Asset Recoveryin in the Criminal Act of Corruption in ASEAN - Rinaldy Amrullah; Rudi Natamiharja (Universitas Sriwijaya, 2020)
The eradication of corruption is not only limited to imprisonment for perpetrators, but also optimally recaptures what has been taken by corruptors (asset recovery). This action needs to be done in order to create a deterrent effect for corruptors and return the state property. Corruption eradication in Southeast Asia, especially by ASEAN member countries, has not shown seriousness. This fact shown from Transparency International report. The majority of ASEAN country member have not been optimal in the orientation of asset recovery in handling corruption cases. How could ASEAN countries eradicate corruption through asset recovery efforts? This study uses a normative comparative method through a qualitative approach. Based on the results of the study found that the level of corruption in Southeast Asia is not the worst, but also not in a safe condition from the threat of corruption and is still classified as an area of concern. Brunei Darussalam, the Philippines, Indonesia and Singapore are among the countries that have succeeded in increasing corruption eradication scores. Indonesia and Thailand become countries that struggle hard to eradicate corruption while Vietnam and Laos are considered to be countries that are still lacking in fighting corruption. Based on the results of the study, it was found that the recovery of corruption assets is still a matter of little concern by the majority of countries except Singapore and Malaysia. In eradicating corruption, particularly in asset recovery, ASEAN needs to have a political will determined and become a law in conducting multilateral cooperation. The agreement must be set forth in the form of regional cooperation that has a strong tie so that this can help efforts to eradicate corruption in ASEAN.